2017
DOI: 10.1016/j.clp.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal Hernia

Abstract: Laparoscopy is a safe and effective technique in the repair of inguinal hernias. This article describes the different laparoscopic herniorrhaphy technique, as well as controversial topics, such as premature infants, contralateral repair, and incarcerated hernias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 51 publications
0
8
0
6
Order By: Relevance
“…Inguinal hernia is one of the most common surgical conditions to occur during infancy, with a reported incidence between 0.8% and 5% 1 . The risk is higher in preterm infants 2 . The most common reason for children to develop a clinical inguinal hernia is a patent processus vaginalis (PPV) or canal of Nuck, leading to the development of a lateral/indirect inguinal hernia 3 .…”
Section: Introductionmentioning
confidence: 96%
“…Inguinal hernia is one of the most common surgical conditions to occur during infancy, with a reported incidence between 0.8% and 5% 1 . The risk is higher in preterm infants 2 . The most common reason for children to develop a clinical inguinal hernia is a patent processus vaginalis (PPV) or canal of Nuck, leading to the development of a lateral/indirect inguinal hernia 3 .…”
Section: Introductionmentioning
confidence: 96%
“…Over the past decade, laparoscopic techniques have been applied widely in the management of common pediatric diseases 14 . Laparoscopic repair in children is considered a safe, effective and convenient technique 15 , 16 , and CPPV can be discovered and repaired to prevent the formation of metachronous inguinal hernia (MIH) 17 . A number of studies have shown that the incidence of CPPV is 50–70% 2 , 3 , but the benefit from the repair is small, perhaps only 1/10 18 , 1/18 19 , or 1/21 20 , according to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, laparoscopic techniques have been applied widely in the management of common pediatric diseases 13 . Laparoscopic repair in children is considered safe, effective and more convenient technique 14,15 , what's more CPPV can be discovered and repaired to prevent the formation of metachronous inguinal hernia (MIH) 16 . A number of studies showed the incidence of CPPV is 50%-70% 2,3 , but the bene t from the repair was tiny, maybe just 1/10 17 ,1/18 18 , 1/21 19 .…”
Section: Discussionmentioning
confidence: 99%